Pengaruh Inflasi, Pemeriksaan Pajak Dan Jumlah Wajib Pajak Terhadap Penerimaan Pajak Penghasilan - Nessa Melisa; Nurhayati . (Jurnal Ekonomi dan Bisnis Digital, 2024)
The population in this study is the entire number of individual taxpayers registered at KPP Pratama Pondok Aren. The sample is part of the population whose characteristics are to be investigated and is considered to represent the entire population. The aim is to understand the factors that influence income tax revenues at the Pondok Aren Pratama Tax Service Office. The context of this research includes the tax environment in the region, which includes tax policies, tax revenue processes, and interactions between tax authorities and taxpayers. Data analysis in this research uses the Partial Least Square (PLS) method, SmartPLS application version 3.3.9. PLS, part of Structural Equation Modeling (SEM), is one of the methods currently used to cover the weaknesses that exist in the regression method. Based on the analysis carried out, inflation has a significant influence on income tax revenues, then the results of the analysis show that tax audits also have a significant influence on income tax revenues and the number of Taxpayers also has a significant influence on income tax revenues at the Pondok Aren Primary Tax Service Office